2003
DOI: 10.25071/1705-1436.167
|View full text |Cite
|
Sign up to set email alerts
|

Community Unionism: Organising for Fair Employment in Canada

Abstract: More Canadian workers are in and out of work or in insecure jobs, prompting the (re)emergence of community unionism. We understand community unionism as a form of mobilization that occupies the centre range along a continuum of community organizing and trade union organizing. After contrasting the currently dominant model industrial unionism to the process-oriented community development mode of organizing, we illustrate the power of drawing on elements of both trade union and community organizing with a case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…These organizational imperatives conflict with changing labor markets and workers' needs. Yet, emerging forms of community-based union representation still offer some hope, as seen in work by the United Food and Commercial Workers with migrant agricultural workers (Cranford & Ladd 2003;Basok 2007), and British Columbia unions with day care workers (Yates 2010).…”
Section: Discussionmentioning
confidence: 98%
“…These organizational imperatives conflict with changing labor markets and workers' needs. Yet, emerging forms of community-based union representation still offer some hope, as seen in work by the United Food and Commercial Workers with migrant agricultural workers (Cranford & Ladd 2003;Basok 2007), and British Columbia unions with day care workers (Yates 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In this conceptual article, the authors analyse the importance of the local knowledge held by local managers working for the subsidiaries of MNEs. Existing research has shown that the knowledge of local managers may be relatively under appreciated by the MNE's headquarters and by expatriate managers (Atamer and Schweiger, 2003;Cranford and Ladd, 2003;Fine, 2005;Goodall and Roberts, 2003). In this article, the authors analyse why such under appreciation of local manager's knowledge may be an even bigger issue for MNEs operating in bottom of pyramid countries (Hahn, 2009).…”
Section: Responsible Leadership At Four Levelsmentioning
confidence: 96%
“…In this way, RAP is akin to a workers' center model seen across North America, including with the Restaurant Opportunities Centers and Migrant Workers Centers (e.g. Black 2012; Choudry and Thomas 2012;Cranford and Ladd 2003). If someone is moving between retail jobs, currently unemployed but looking for work in retail, or is a long-serving worker in a nonunionized store, he or she can nevertheless contribute to and benefit from RAP.…”
Section: Occupation/sector-based Associationmentioning
confidence: 99%